Anal cancer and precancerous lesions: a call for improvement. (April 2021) - Albuquerque, Andreia; Nathan, Mayura; Cappello, Carmelina; Dinis-Ribeiro, Mário
Summary: Anal squamous cell carcinoma is the most common type of anal cancer and is largely associated with anal human papillomavirus infection. The incidence of anal squamous cell carcinoma is increasing, and although still uncommon in the general population, a high incidence has been noted in specific population groups (eg, patients with HIV, men who have sex with men [MSM], recipients of solid organ transplants, women with genital neoplasia, and patients with systemic lupus erythematosus or inflammatory bowel disease). The higher incidence among individuals who are HIV-positive makes anal squamous cell carcinoma one of the most common non-AIDS-defining cancers among HIV-positive individuals. Anal cancer screening in high-risk groups aims to detect high-grade squamous intraepithelial lesions, which are considered anal precancerous lesions, and for which identification can provide an opportunity for prevention. A blind anal cytology is normally the first screening method, and for patients with abnormal results, this approach can be followed by an examination of the anal canal and perianal area under magnification, along with staining—a technique known as high-resolution anoscopy. Digital anorectal examination can enable early anal cancer detection. Several societies are in favour of screening for HIV-positive MSM and recipients of transplants. There are no current recommendations for screening of anal precancerous lesions via endoscopy, but in high-risk groups, a careful observation of the squamocolumnar junction should be attempted. Several treatments can be used to treat high-grade squamous intraepithelial lesions, including argon plasma coagulation or radiofrequency ablation, which are largely limited by high recurrence rates. Gastroenterologists need to be aware of anal squamous cell carcinoma and anal precancerous lesions, given that patients at high risk are frequently encountered in the gastroenterology department. We summarise simple procedures that can help in early anal squamous cell carcinoma detection.